East and West in late antiquity: invasion, settlement, ethnogenesis and conflicts of religion - Liebeschuetz, J. H. W. G. (Impact of Empire, 2015)
"East and West in Late Antiquity combines published and unpublished articles by emeritus professor Wolf Liebeschuetz. The collection concerns aspects of what Gibbon called 'the Decline and Fall of the Roman Empire.' This interpretation is now much criticized, but the author agrees with Gibbon. Topics discussed are defensive strategies, the settlement inside the Empire of invaders and immigrants, and the modification of identities with the formation of new communities. Liebeschuetz is interested in both the eastern and the western halves of the Empire. In the East he is particularly concerned with Syria, the expansion of settlement up to the edge of the desert, and Christianisation. The book ends with an examination of the role of the Christian Arab Ghassanids in the defense of the Syrian provinces in the century leading up to the conquest of the provinces by the Islamic Arabs"--Provided by publisher